2016
DOI: 10.3389/fnins.2016.00597
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Resonance Controlled Upregulation of Internal Noise after Hearing Loss as a Putative Cause of Tinnitus-Related Neuronal Hyperactivity

Abstract: Subjective tinnitus is generally assumed to be a consequence of hearing loss. In animal studies it has been demonstrated that acoustic trauma induced cochlear damage can lead to behavioral signs of tinnitus. In addition it was shown that noise trauma may lead to deafferentation of cochlear inner hair cells (IHC) even in the absence of elevated hearing thresholds, and it seems conceivable that such hidden hearing loss may be sufficient to cause tinnitus. Numerous studies have indicated that tinnitus is correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(145 citation statements)
references
References 98 publications
9
130
0
6
Order By: Relevance
“…5, right panel) which is in line with the increased activity in the medial geniculate body (MGb) reported after noise exposure (Kalappa et al, 2014). It seems likely that increased thalamic activation of ACx is the result of mechanisms of compensatory, homeostatic plasticity (Mossop et al, 2000;Schaette and Kempter, 2006;Noreña, 2011;Tighilet et al, 2016) or stochastic resonance (Krauss et al, 2016(Krauss et al, , 2018 within the subcortical auditory pathway (Eggermont, 2017a). This conclusion is further supported by our layerspecific analysis, demonstrating that early sink activity in both thalamocortical-recipient layers III/IV and Vb/VIa was significantly increased after recovery (Fig.…”
Section: Chronic Effects Of Sound Trauma On Circuit-level Activity Insupporting
confidence: 69%
See 2 more Smart Citations
“…5, right panel) which is in line with the increased activity in the medial geniculate body (MGb) reported after noise exposure (Kalappa et al, 2014). It seems likely that increased thalamic activation of ACx is the result of mechanisms of compensatory, homeostatic plasticity (Mossop et al, 2000;Schaette and Kempter, 2006;Noreña, 2011;Tighilet et al, 2016) or stochastic resonance (Krauss et al, 2016(Krauss et al, , 2018 within the subcortical auditory pathway (Eggermont, 2017a). This conclusion is further supported by our layerspecific analysis, demonstrating that early sink activity in both thalamocortical-recipient layers III/IV and Vb/VIa was significantly increased after recovery (Fig.…”
Section: Chronic Effects Of Sound Trauma On Circuit-level Activity Insupporting
confidence: 69%
“…Exposure to high sound levels can severely damage the peripheral sensory receptor epithelia within the cochlea which presents the most reasonable initial factor for such pathological disturbances: Cochlear damage causes altered auditory processing and, in consequence, may lead to compensatory and/or erroneous functional map plasticity in higher sensory brain areas, as for instance the auditory cortex. Such maladaptive map plasticity has been proposed to underlie the development of central tinnitus (Eggermont, 2003;Engineer et al, 2011), although these classical models of tinnitus development have recently been challenged by alternative models (Schaette and Kempter, 2006;Krauss et al, 2016). In humans, as well as in animal models, plastic changes of the tonotopic organization of the auditory cortex (ACx) have been found after noise exposure (Muhlnickel et al, 1998;Eggermont and Komiya, 2000;Dietrich et al, 2001;Norena, 2005;Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One well accepted theory is homeostatic plasticity, which describes central gain as a neural compensatory mechanism for hearing loss (Auerbach, Rodrigues et al 2014). More recently, computational modeling has suggested that the central gain phenomena may result from stochastic resonance (Krauss, Tziridis et al 2016), a phenomenon where signal intensity is enhanced with the introduction of noise to a system. This phenomenon has been shown to exist within the auditory system of humans (Zeng, Fu et al 2000), and may play a primary role in the response changes observed in the present study.…”
Section: Adaptive Gain Controlmentioning
confidence: 99%
“…However, until recently the underlying neural processes remained rather elusive. In recent studies, we argued that a processing principle called adaptive stochastic resonance is exploited by the auditory system in order to continuously maintain optimal sensitivity even to highly variable sound pressure levels and changing statistics of the acoustic environment (Krauss et al, 2016;2018). The term stochastic resonance refers to a phenomenon, where a signal of arbitrary kind, which is too weak for a certain sensor for being detected, can be made detectable by adding a random signal, i.e.…”
Section: Introductionmentioning
confidence: 99%